1991
DOI: 10.1148/radiology.179.3.2027984
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass in healthy children: measurement with quantitative DXA.

Abstract: Dual-energy x-ray bone densitometry was used to study the lumbar vertebral bone mass in 218 healthy children (134 girls and 84 boys) aged 1-19 years. Vertebral bone mass increased with weight, age, and pubertal Tanner stage. Results of multiple regression analyses showed that Tanner stage and weight were the best predictive indicators of bone mass and bone mineral density. The influences of age, sex, race, physical activity, and diet were not significant when Tanner stage and weight were controlled. Two tables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(122 citation statements)
references
References 0 publications
10
108
0
4
Order By: Relevance
“…Mechanical loading during weight-bearing activities stimulates bone formation, and multiple studies in healthy adolescents 8,[71][72][73] and in those with anorexia nervosa [74][75][76][77] have demonstrated that BMD is directly correlated with BMI. Lean body mass is most strongly associated with BMD, 78 but increased adiposity can also be associated with increased fracture risk.…”
Section: Body Weightmentioning
confidence: 99%
“…Mechanical loading during weight-bearing activities stimulates bone formation, and multiple studies in healthy adolescents 8,[71][72][73] and in those with anorexia nervosa [74][75][76][77] have demonstrated that BMD is directly correlated with BMI. Lean body mass is most strongly associated with BMD, 78 but increased adiposity can also be associated with increased fracture risk.…”
Section: Body Weightmentioning
confidence: 99%
“…The Z-score of the lumbar spine BMD was determined using our institution's normative data based on the report by Southard et al from our institution that studied 218 healthy children, age 1-19 years [18]. The lumbar BMD is adjusted for weight and pubertal status, as multiple regression analyses in this study showed that Tanner stage and weight were the best predictive indicators of bone mass and BMD in children [18]. Total body bone mineral content (BMC) was determined for patients without hardware (e.g.…”
Section: Bone Mineral Density Measurementmentioning
confidence: 99%
“…Glucocorticoid [26][27][28][29][30][31][32][33][34][35] and methotrexate [36][37][38][39] treatment and cranial irradiation [40][41][42] have been inconsistently associated with the risk of osteopenia. However, findings of these studies have been limited by the generally small and heterogeneously treated patient cohorts.…”
Section: 425mentioning
confidence: 99%